2022
DOI: 10.1093/oncolo/oyac056
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Characteristics, and Predictors of Cardiovascular Immune-Related Adverse Events Associated with Immune Checkpoint Inhibitors

Abstract: Background Cardiovascular immune-related adverse events (CV–irAEs) associated with immune checkpoint inhibitors (ICIs) may have been underreported given that most previous reports were retrospective. We aimed to evaluate the incidence, clinical characteristics, and predictors of CV–irAEs and determine the feasibility of serial cardiac monitoring using a combination of B-type natriuretic peptide, cardiac troponin T, and electrocardiogram for the prediction of future symptomatic (grade ≥2) CV–i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Patients with non-small-cell lung cancer, receiving ICI monotherapy, were investigated by Isawa et al in a prospective observational study [57]. One hundred and twenty-nine patients were enrolled and received serial cardiac monitoring, i.e., hs-TnT, BNP, and an ECG at baseline and every four to six weeks thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non-small-cell lung cancer, receiving ICI monotherapy, were investigated by Isawa et al in a prospective observational study [57]. One hundred and twenty-nine patients were enrolled and received serial cardiac monitoring, i.e., hs-TnT, BNP, and an ECG at baseline and every four to six weeks thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…If results are normal, these tests can be spaced to every three doses [43][44][45]. It is worth mentioning that troponin I and T are not expressed in the skeletal muscle of healthy adult patients, but troponin T is found within the fetal skeletal muscle.…”
Section: Cardiac Functionmentioning
confidence: 99%
“…We suggest performing a clinical evaluation, an electrocardiogram, a measurement of serum troponin T and, where available, a troponin I at baseline in all patients prior to ICI treatment initiation and up to the 4th administration. If results are normal, these tests can be spaced to every three doses [ 43 45 ]. It is worth mentioning that troponin I and T are not expressed in the skeletal muscle of healthy adult patients, but troponin T is found within the fetal skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…A study of data from eight clinical sites showed myocarditis prevalence to be 1.14% after ICI treatment, with a median time of onset of 34 days after starting ICIs 5 . However, a recent study suggested that cardiac irAEs may be underreported due to failure to diagnose asymptomatic cases 6 . Of note, the mortality rate of ICI-related myocarditis is reportedly as high as 50% 7 .…”
Section: Introductionmentioning
confidence: 99%